Avaliação da ação profilática da vacina de DNA-hsp65 na neurotuberculose experimental - Santos, José Gilmar Costa (2016)
Tuberculosis (TB) is caused by Mycobacterium tuberculosis and is a global public health problem and is considered one of the deadliest infectious diseases of the world. It is estimated that about one third of the world population is infected. TB in Central Nervous System (CNS) is one of the most severe forms of the disease, more common in children aged six months to five years old and among individuals with immunosuppression, particularly those with Acquired Immunodeficiency Syndrome (AIDS). Neurotuberculosis (NTB) is associated with a high rate of mortality in children and permanent neurological sequelae in many survivors. Currently, the way to prevent TB is BCG (Bacilo Calmette-Guérin) vaccination, however, it has limitations because it only protects children and only prevents severe forms of TB, besides presenting variable protection of 0-75%. This shows the need to develop a more effective vaccine to fight TB. One of the most promising alternatives for TB is the DNA-hsp65 vaccine, made of a plasmid DNA containing the gene encoding the heat shock protein 65 kDa of mycobacteria (M. leprae). Although, it has not studied the protective effect of DNA-hsp65 vaccine against TB in the CNS, which is the most severe form of the disease and compromises the neural tissue. Thus, we evaluated the prophylactic effect of DNA-hsp65 vaccine in experimental neurotuberculosis. C57BL/6 mice were used by three experimental groups, where one of them was immunized only with plasmideal pVAX vector (vector group) by intramuscular administration of three doses every two weeks, another group received only PBS (PBS group) and the third group DNA was immunized with hsp65-pVAX plasmideal (vaccinated group). Thirty days after the last dose, the animals of each group were challenged with H37Rv laboratorial strain of Mycobacterium tuberculosis intracerebroventricularly by stereotaxy. Thirty days after the challenge with the bacilli, the mice were sacrificed and their brains and lungs removed. These organs were analyzed using histological sections stained with hematoxylin and eosin. It was also determined amounts of colony forming units (CFU) present in the brains of animals in all groups. The results show that animals of the vaccinated group exhibited brain and lung with discrete lesions of the vector and PBS groups. Furthermore, we noticed a reduced number of bacilli in the brains of animals in the vaccinated group. Therefore, our results suggest that DNA-hsp65 vaccine (pVAX-hsp65) is promising in the prevention of injuries caused by bacillus in the CNS.